Preálgebra y pensamiento algebraico en educación básica - Gutiérrez, Ángel (2025)
Based on experimental and practical work, a teaching methodology is presented in the context of pre-algebra and based on geometric pattern problems. By solving these types of problems themselves, teachers will discover how the main concepts at the beginning of algebra teaching emerge naturally, contextually, and meaningfully. Furthermore, by bringing this teaching methodology into their classrooms, they will see how it helps their students begin learning algebra and overcome the difficulties they encounter in understanding the meanings of the = sign, letters, and equations. In this text, I will introduce pre-algebra and algebraic thinking. Next, I will analyze the structure of geometric pattern problems and their learning objectives. Third, I will present examples of student responses, whose analysis will show the variety of possible solution processes and the diversity of response styles corresponding to students who progress at different rates in their understanding of basic algebraic concepts.